FAKTOR FAKTOR YANG MEMPENGARUHI KEJADIAN DIABETES MELITUS GESTASIONAL - Wati, Risna; Dahliah, Dahliah; Abdullah, Farid (Universitas Pahlawan, 2024)
Gestational Diabetes Melitus (GDM) is a condition in which women who have not previously been diagnosed with diabetes then show high glucose levels during pregnancy at the 24th week of pregnancy and blood sugar levels will return to normal after pregnancy. The prevalence of GDM has continued to increase over the last 20 years. The International Diabetes Federation (IDF) reports that 16.7% (21.1 million) of live births to women in 2021 experienced hyperglycemia in pregnancy. Of this amount, 80.3% was caused by gestational diabetes mellitus. Gestational diabetes mellitus is associated with an increased risk of perinatal mortality and morbidity and is a major public health problem. Various risk factors have been identified as predictors of GDM, such as advanced maternal age, family history of diabetes, obesity, and low physical activity. Beside that, maternal factors with macrosomia and multiparity also increase the risk of GDM in pregnant women.